School environment role towards elementary school students’ moral and cultural literacy - Ika Maryani; Ianah Hasnatul Prawestri; Dwi Sulisworo; Siti Urbayatun; Suyatno Suyatno; Caraka Putra Bhakti (Journal of Education and Learning (EduLearn), 2019)
This study aims to determine the role of the school environment on moral and cultural literacy of elementary school students. This is descriptive qualitative research. Data collection techniques are observation, interviews, questionnaire, and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. Data validity using triangulation. Triangulation is to ensure the data validity that takes into consideration aspects of credibility, transferability, dependability, and confirmability. The subjects are 3 teachers and 27 students of 4th, 5th and 6th grade in Muhammadiyah School of Sleman Regency. The results of this study are (1) teachers-students’ relationships have role to foster the character of honesty, fairness, caring, and teachers as role model for students; (2) students-students’ relationships also have role to habituate good behavior to students; (3) school discipline contributes to the students’ moral and cultural formation such as self-awareness, honesty, justice, responsibility, obedience to the rules, good commitment and unfazed by the changing era; (4) these learning implements have role in self-awareness, responsibility and care, because the teaching implements provided by the teachers becomes the students’ responsibility.